Diplomacy and war at NATO the secretary general and military action after the Cold War - Hendrickson, Ryan C., 1969- (University of Missouri Press, 2006)
"Examines the first four post-Cold War secretaries general-Manfred Wörner, Willy Claes, Javier Solana, and George Robertson. Drawing on interviews with former NATO ambassadors, alliance military leaders, and senior NATO officials, Hendrickson demonstrates that the secretary general is often the central diplomat in generating cooperation within NATO"--Provided by publisher.